2022
DOI: 10.1186/s12968-021-00832-2
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular flow analysis and its association with exertional capacity in repaired tetralogy of Fallot: 4D flow cardiovascular magnetic resonance study

Abstract: Background Four-dimensional (4D) flow cardiovascular magnetic resonance (CMR) allows quantification of biventricular blood flow by flow components and kinetic energy (KE) analyses. However, it remains unclear whether 4D flow parameters can predict cardiopulmonary exercise testing (CPET) as a clinical outcome in repaired tetralogy of Fallot (rTOF). Current study aimed to (1) compare 4D flow CMR parameters in rTOF with age- and gender-matched healthy controls, (2) investigate associations of 4D f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…Written informed consent was obtained from all subjects. Part of the study population was included in previous studies to investigate the impact of age, sex and ethnicity on left ventricular (LV) flow components and kinetic energy [ 18 ], and associations of 4D flow parameters with RV functional, remodelling and CPET outcome in repaired tetralogy of Fallot patients [ 19 ]. From June 2017 to February 2021, 56 PAH patients and 141 healthy subjects were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all subjects. Part of the study population was included in previous studies to investigate the impact of age, sex and ethnicity on left ventricular (LV) flow components and kinetic energy [ 18 ], and associations of 4D flow parameters with RV functional, remodelling and CPET outcome in repaired tetralogy of Fallot patients [ 19 ]. From June 2017 to February 2021, 56 PAH patients and 141 healthy subjects were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormalities in global longitudinal strain and circumferential strain, including biventricular dis-synchrony in RTOF have been well-documented ( 25 , 28 ). More recently, the flow topologies by 4D flow have been directly correlated to exercise capacity ( 5 , 29 ). These RTOF studies point to the concept of cardiac function as a multi-parameter, three-dimensional phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified good agreement between 4D flow CMR and the reference method for peak flow velocity assessment, namely pulse-wave doppler TTE (5,6,7). Four-dimensional flow CMR can overcome many of the limitations of Doppler TTE and may improve the accuracy of transvalvular peak velocity quantification (2,(11)(12)(13). Despite the promising capabilities of 4D J o u r n a l P r e -p r o o f flow CMR technology, its use in clinical practice has been hampered by lengthy post-processing times and the lack of validated software tools to accurately quantify flow velocities.…”
Section: Introductionmentioning
confidence: 97%